Survey of injuries among Slovenian sport climbers - Hlebš, S.; Brezovar, T. (The Journal of Sports Medicine and Physical Fitness, 2026)
BACKGROUND: Rock climbing is associated with a high risk of musculoskeletal injuries, yet limited data exist for Slovenian sport climbers. Understanding the prevalence, types, and mechanisms of injuries is essential for developing targeted prevention strategies.